Characteristic of Central Nervous System Tumours from 2011-2015: A Single Institution Study - Febrihardita Dwinovitch; Nadya Aisyah Widowati; Erna Kristiani (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Background: Central nervous system (CNS) tumours affect the quality of life of patients since its neurological deficits. Data from Globocan 2012 reveals that there are 256,000 cases of CNS tumour. Epidemiology of the CNS tumours is very important for diagnosis and treatment, but data in Indonesia is still not fully reported.Objective: The aim of this study was to determine the exact amount of the incidence, histologic type of the tumour and the characteristic of patient in our institution.Methods: This is an observational study, all pathology report of CNS tumours that underwent surgery at Siloam Hospitals Lippo Village from 2011 until 2015. We classified based on gender, age, location of the tumour, and the histologic type according to WHO Classification of CNS tumour 2007.Results and Discussion: There were 913 patients of CNS tumours from 2011 until 2015. The most common tumours were meningioma (32.96%) followed by glioma (21.35%) and pituitary adenoma (16.10%). In meningioma, most occur in women, 41 - 50 years old, located in the frontal region and the most common subtype is transitional meningioma. In glioma, most occur in men, 31 - 40 years old, located in the frontal region and the most common subtype is glioblastoma. In adenoma hipofisis, most occur in men, 41 - 50 years old.Conclusion: The result of this study was accordance with the literature so this data could be a reference for further research.